The influence of frequency social media use on the level FOMO teenagers in social media era - Anjani, Sefylia; Widyatama, Rendra (COMMICAST, 2023)
In this era of social media, fear of missing out (FOMO) is a common phenomenon that occurs in society, including adolescents. FOMO is a psychological phenomenon in the form of anxiety and a sense of being left behind from social activities that develop in society. FOMO can become a psychological problem if it is excessive or persistent. Some experts argue that FOMO is not related to gender but rather to personal characteristics and other causes, including the frequency of social media use that has become an integral part of people’s lives. This study investigates the influence of the frequency of social media use on the level of FOMO in adolescents in the social media era. The study used a quantitative approach with data collection through questionnaires to adolescents actively using social media. Researchers sent questionnaires online to respondents with the inclusion criteria of men and women actively using social media and willing to be research respondents. There were 300 respondents involved in this study. Based on the t-test statistical analysis with a significant level of 0.05, the researcher concluded that the frequency of social media use has an influence on FOMO. The results of this study are significant findings related to FOMO studies that are useful for various interests, especially for adolescent education, to prevent the negative impact of FOMO in the form of stress and emotional disorders.